Correction to: Comparing health insurance data and health interview survey data for ascertaining chronic disease prevalence in Belgium - Finaba Berete; Stefaan Demarest; Rana Charafeddine; Olivier Bruyère; Johan Van der Heyden (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.